What Are the Cost Implications of Robotic Surgery? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Robotic-assisted surgery (RAS) has emerged as a transformative force in modern medicine, offering enhanced precision, improved dexterity, and minimally invas...
Keywords: AI in Surgery and Robotics; Implications; Robotic; Surgery; Healthcare